Al Tafsir al Munir : fi al 'aqidah wa al shari'ah wa al manhaj - Wahbah al_Zuhayli (Dar al Fikr, 1991)
ws.jl.1-2,.c.1, jl.3-12-16.c.1-2/why, .32-.48 (jld.1=c.1, jld. 2-15=c.3, jld. 16 (faharis 1, c.1), jld. 17 (faharis 2, c.1)